(untitled) (Jahangirnagar University Journal of Biological Sciences, 2018)
Eight commercial insecticides-chlorpyrifos, bifenithrin, fenitrothion, cypermethrin, deltamethrin, cyhalothrin, dimethoate and malathion under the brand name of Dursban 20 EC, Bifenithrin 20 EC, Sumithion 50 EC, Relothrin 10 EC, Marker 2.5 EC, Reeva 2.5 EC, Tafgar 40 EC and Hilthion 57 EC, respectively were tested in laboratory at room temperature to evaluate the effective level against 3rd instar larvae of Culex quinquefasciatus Say from Savar area of Dhaka. The LC50 values for chlorpyrifos, bifenithrin, fenitrothion, cypermethrin, deltamethrin, cyhalothrin, dimethoate and malathion were 0.127, 297.474, 0.308, 0.327, 0.198, 0.189, 0.054 and 0.031 ppm respectively and their corresponding LC90 values were found to be 0.984, 2582, 0.041, 3.298, 0.728, 1.705, 0.192 and 0.030 ppm respectively. The relative potency of these insecticides tested to the larvae was found in respect to their LC50 values in the order of Hilthion 57 EC (malathion)> Tafgar 40 EC (dimethoate)> Dursban 20 EC (chlorpyrifos)> Reeva 2.5 EC (cyhalothrin)> Marker 2.5 EC (deltamethrin)> Sumithion 50 EC (fenitrothion)> Relothrin 10 EC (cypermethrin)> Bifenithrin 20 EC. However, the relative potency of these insecticides tested to the larvae was found in respect to their LC90 values in the order of Hilthion 57 EC (malathion)> Sumithion 50 EC (fenitrothion)> Marker 2.5 EC (deltamethrin)> Dursban 20 EC (chlorpyrifos)> Tafgar 40 EC (dimethoate)> Reeva 2.5 EC (cyhalothrin)> Relothrin 10 EC (cypermethrin)> Bifenithrin 20 EC. Taken together, the insecticide-malathion (Hilthion 57 EC) was found to be the most effective against the third instar larvae of Cx. quinquefasciatus in Savar area. Jahangirnagar University J. Biol. Sci. 7(2): 21-32, 2018 (December)